2003
DOI: 10.4049/jimmunol.171.11.6112
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and Phenotype of an Innate Th1 Cell: Role of Cytokines and the p38 Kinase Pathway

Abstract: We have explored the phenotype and regulation of Th1 cell activation by the cytokines IL-12 and IL-18. We demonstrate that these two cytokines selectively induce IFN-γ in a differentiated Th1 cell population through the previously described p38 mitogen-activated protein (MAP) kinase pathway. Using a highly selective p38 MAP kinase inhibitor, we demonstrate that it is possible to block IFN-γ induction from activated, differentiated Th1 cells via p38 MAP kinase without disrupting the activation and differentiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 29 publications
(21 reference statements)
1
33
0
Order By: Relevance
“…Interestingly, IL-18 directly induces division and cytokine secretion by effector or memory T cells in the absence of recall Ag (29,58). However, naive T cells do not express the IL-18R (27), and therefore it was surprising that IL-18 boosted the CD4 T cells in our model.…”
Section: Discussionmentioning
confidence: 93%
“…Interestingly, IL-18 directly induces division and cytokine secretion by effector or memory T cells in the absence of recall Ag (29,58). However, naive T cells do not express the IL-18R (27), and therefore it was surprising that IL-18 boosted the CD4 T cells in our model.…”
Section: Discussionmentioning
confidence: 93%
“…However, the role of p38 in polarization of Th1 cells is not as clear. Although the p38 inhibitors SB203580 and SC-409 blocked cytokine-mediated IFN-␥ production by Th1 cells, they did not prevent the activation, differentiation, or proliferation of new Th1 cells (5). Recently generated p38␣ Ϫ/Ϫ T and B cells developed and proliferated normally (7), and p38␣-deficient CD4 ϩ T cells differentiated into Th1 effector cells in vitro and expressed normal levels of IFN-␥ when restimulated through the TCR (8), suggesting that T cell p38␣ is dispensable for Th1 development.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, however, p38␣ Ϫ/Ϫ T and B cells were found to develop normally (7), and p38␣-deficient CD4 ϩ T cells expressed normal levels of IFN-␥ when differentiated in vitro under Th1-polarizing conditions (8). It was also reported that p38 inhibitors blocked cytokine-induced Th1 IFN-␥ production without disrupting the activation and differentiation of new Th1 effector (5). Hence, there is good evidence of the importance of p38 in Th1 IFN-␥ production, but the role of p38 in Th1 cell differentiation needs to be clarified.…”
Section: Gadd45␣ Regulates P38-dependent Dendritic Cell Cytokinementioning
confidence: 99%
See 1 more Smart Citation
“…13 On binding of IL-18 to IL-18Ra, IL-18Rb is recruited and induces signalling pathways common to other IL-1R family members such as myeloid differentiation 88 (MyD88), IL-1R-associated kinase (IRAK), tumour necrosis factor receptor-associated factor 6 (TRAF6), nuclear factor kB (NF-kB), and other downstream effectors. [14][15][16][17][18][19] IL-18 also has a soluble decoy receptor/inhibitor -IL-18-binding protein (IL-18BP). IL-18BP binds to IL-18 preventing it from associating with IL-18R and therefore inhibiting IL-18-induced IFN-g production.…”
Section: Methods Of Actionmentioning
confidence: 99%